Anticancer Drug-Related Nonvalvular Atrial Fibrillation: Challenges in Management and Antithrombotic Strategies - Tufano, Antonella; Galderisi, Maurizio; Esposito, Luca; Trimarco, Valentina; Sorriento, Daniela; Gerusalem, Guy; Picardi, Marco; Lancellotti, Patrizio; Pane, Fabrizio (Seminars in Thrombosis and Hemostasis, 2018)
Cancer patients may experience nonvalvular atrial fibrillation (AF) as a manifestation of cardiotoxicity. AF may be a direct effect of a neoplasm or, more often, appear as a postsurgical complication, especially after thoracic surgery. AF may also develop as a consequence of anticancer therapy (chemotherapy or radiotherapy), a condition probably underestimated. Cancer patients with AF require a multidisciplinary approach involving oncologists/hematologists, cardiologists, and coagulation experts. An echocardiogram should be performed to detect possible abnormalities of left ventricular systolic and diastolic function, as well as left atrial dilation and the existence of valvular heart disease, to determine pretest probability of sinus rhythm restoration, and identify the best treatment. The choice of antiarrhythmic treatment in cancer patients may be difficult because scanty information is available on the interactions between anticancer agents and antiarrhythmic drugs. A careful evaluation of the antithrombotic strategy with the best efficacy/safety ratio is always needed. The use of vitamin K antagonists (VKAs) may be problematic because of the unpredictable therapeutic response and high bleeding risk in patients with active cancer who are undergoing chemotherapy and who may experience thrombocytopenia and changes in renal or hepatic function. Low molecular weight heparins (in particular for short and intermediate periods) and non-VKA oral anticoagulants (NOACs) should be preferred. However, the possible pharmacological interactions of NOACs with both anticancer and antiarrhythmic drugs should be considered. Based on all these considerations, antiarrhythmic and anticoagulant therapy for AF should be tailored individually for each patient.
Keywords: atrial fibrillation; cancer; drug interaction; stroke; anticoagulants